The Growth of Chlorella sp. With Varying Nutrient Concentration - Intanurfemi Hismayasari; Ernawati Ernawati; Agung Setia Abadi; Asthervina Widyastami Puspitasari (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
The aim of this study was to determine the effect of differences addition of culture medium concentrations on the growth of microalgae type Chlorella sp. Samples were obtained from the Center for Brackish Water Cultivation Fisheries (BBPBAP), Jepara. This research was conducted at the Laboratory of Nutrition and Natural Feed Sorong Marine and Fisheries Polytechnic with an experimental method using four treatments with addition of walne medium, there were A (adding only at the beginning of cultivation); treatment B (adding every day); C (adding every two days), and treatment; D (adding every three days). The cell growth performance was significantly found in treatment C with the addition of nutrients every two days with a peak cell density of Chlorella sp was 2,628,450 cells / ml. There is a need for mass culture assay to determine the level of effectiveness and efficiency.